ANALYSIS OF NUTRITIONAL STATUS AND PHYSICAL FITNESS LEVELS AMONG STUDENTS AT STATE SENIOR HIGH SCHOOL 4 WIRA BANGSA MEULABOH - Iqram, Muhammad; Karimuddin, Karimuddin; Rinaldy, Alfian; Jafar, Muhammad; Syukriadi, Amanda (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2025)
Nutritional status is a crucial element that supports student achievement in school because the body needs a healthy and balanced diet. Nutrition includes carbohydrates, proteins, and fats that provide energy, repair tissues, and protect organs. Physical fitness reflects the physical ability to perform activities efficiently and with endurance. Therefore, nutritional status and physical fitness work synergistically to help children achieve maximum learning performance and physical activity. The objectives of this study are: (1) To determine the nutritional status of students at SMA Negeri 4 Wira Bangsa Meulaboh, (2) To determine the physical fitness level of students at SMA Negeri 4 Wira Bangsa Meulaboh. This study uses a quantitative approach with a descriptive type. The sampling technique used purposive sampling, resulting in a sample of 50 students from SMA Negeri 4 Wira Bangsa Meulaboh. Data collection techniques used tests, as follows: (1) nutritional status, and (2) physical fitness. The results of the data analysis can be summarized as follows: (1) The nutritional status test obtained an average score of 20.88 with the following details: (a) the nutritional status of male students was classified as mildly underweight 8 (67%), while (b) the nutritional status of female students was classified as mildly underweight 19 (50%), and (2) The physical fitness test obtained an average score of 16.88 with the following details: (a) the level of physical fitness in male students was classified as good 8 (67%), followed by (b) the level of physical fitness in female students was classified as moderate 30 (79%).